Faktor Yang Berhubungan Dengan Risiko Kecelakaan Kerja Pada Bagian Pengolahan Makanan Di Instalasi Gizi RSUD Bahteramas Provinsi Sulawesi Tenggara Tahun 2023 - Nurul Khairunnisa; Harleli Harleli; Indah Ade Prianti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Work accidents are adverse occurrences that can interrupt operational operations and arise from hazardous behaviors and conditions. According to the ILO data from 2018, over 2.78 million workers perish annually as a result of work-related accidents. Among these fatalities, around 2,000 (or 13.7%) are caused by work accidents, while the remaining 4 million (or 86.3%) are attributed to occupational diseases. One of these is located in the nutrition installation division of Bahteramas Regional Hospital, in the Southeast Sulawesi Province. The objective of this study is to ascertain the factors responsible for work-related accidents among food processing workers at the Nutrition Installation of Bahteramas Regional Hospital in Southeast Sulawesi Province. This study is a descriptive survey that aims to identify the elements contributing to risky actions and unsafe situations leading to work accidents in the food processing area of the Nutrition Installation at Bahteramas Regional Hospital, Southeast Sulawesi Province. The research sample comprised 37 individuals, selected from the population of workers in the food processing department at the Nutrition Installation at RSUD dr. Soedarso, Kalimantan Province, Bahteramas, Southeast Sulawesi Province. The majority of respondents demonstrated a satisfactory level of knowledge. Out of the total respondents, 12 individuals (66.7%) reported no work accidents. Among those who experienced work accidents, 66.7% exhibited poor work behavior. The compliant category showed a high usage of Personal Protective Equipment (PPE). Out of the total respondents, 12 individuals (33.3%) did not have any work accidents, while 24 individuals (66.7%) did encounter work accidents. The primary aim of this study is to identify the characteristics that contribute to the likelihood of work-related accidents among food processing employees at the nutrition facility in Bahteramas Regional Hospital, located in the Southeast Sulawesi Province.